Slurry, preparation method and application thereof, and high-thermal-conductivity polyimide film

By surface modification of Si4N3 and blending with graphene nanosheets and covering the graphene surface, the problem of poor thermal conductivity of polyimide films is solved, and the combination of high thermal conductivity and electrical insulation is achieved, the thermal conductivity coefficient is increased by more than 20 times, widening the application range.

CN119798658APending Publication Date: 2025-04-11SHANDONG JUCAI POLYMER MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411940438.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing polyimide films have poor thermal conductivity, which affects the performance and service life of electronic devices. Moreover, the dispersion of silicon nitride in polymer materials is poor. The conductive properties of graphene improve the thermal conductivity of the film but also increase the conductivity, limiting its application.

Method used

The surface modification of Si4N3 and blended with graphene nanosheets, coated the surface of the graphene nanosheets by electrostatic adsorption, and finally the mixed liquid was added to the polyamic acid solution to prepare a high thermal conductivity PI film.

Benefits of technology

It achieves a combination of high thermal conductivity and electrical insulation, and has increased the thermal conductivity by more than 20 times, solving the problem of slow heat dissipation of polyimide films, broadening its application range, and simplifying the preparation process and good repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798658A_ABST
    Figure CN119798658A_ABST
Patent Text Reader

Abstract

The invention discloses slurry, a preparation method and application thereof and a high-thermal-conductivity polyimide film, and belongs to the technical field of polymer film materials. An anhydride group in a dianhydride monomer reacts with an amino-terminated group in a diamine monomer to prepare a polyamide acid solution, and the polyamide acid solution is blended with a surface-modified silicon nitride / graphene nanosheet mixed solution to finally obtain the high-thermal-conductivity polyimide film material. The silicon nitride is subjected to surface modification, so that the dispersity of the silicon nitride in a polyimide matrix is improved, and the problem that the silicon nitride is easy to agglomerate is solved. The surface of the graphene nanosheet is coated with the surface-modified silicon nitride through electrostatic adsorption, so that the thermal conductivity of the polyimide film is improved, the formation of a conductive network is avoided, the polyimide film with good thermal conductivity and electrical insulation property is obtained, a brand new scheme is provided for preparing electronic packaging materials with high thermal conductivity and electrical insulation property, and the application prospect is wide. And the application range of the polyimide film is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer film materials, and in particular relates to a slurry, a preparation method and application thereof, and a high thermal conductivity polyimide film. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Polyimide (PI) refers to an aromatic heterocyclic polymer compound containing an imide ring (-CO-NH-CO-) in the main chain of the molecule. It is a special polymer material that has been industrialized. Due to its excellent thermal stability, mechanical properties and good dielectric properties, polyimide (PI) is widely used in microelectronic devices, electronic packaging and aerospace industries, and is known as "one of the most promising engineering plastics in the 21st century." However, conventional PI has the defect of poor thermal conductivity. When used as an electronic device, it cannot dissipate heat in time, which seriously affects the performance and service life of the device. Therefore, how to achieve thermal conductivity of PI-based materials has become a huge challenge.

[0004] Among them, silicon nitride (Si4N3) has the characteristics of high thermal conductivity, high electrical breakdown strength, low hygroscopicity, excellent oxidation resistance and corrosion resistance, and is an ideal filler for preparing high thermal conductivity and electrical insulation polymer materials. However, its poor dispersibility in polymer materials limits its application.

[0005] Graphene is a reinforcing material with excellent performance, excellent mechanical properties, excellent physical thermal conductivity (thermal conductivity is 5300W / m·K) and excellent chemical stability. It is widely used in aerospace, solar power generation, nanomaterials, biomedicine and other fields, and is one of the ideal fillers for preparing thermal conductive polymer materials. Due to the excellent conductivity of graphene, adding it to polyimide film can improve thermal conductivity, but the conductivity is also greatly improved, which limits the application of polyimide in high thermal conductivity and high insulation electronic packaging materials.

[0006] Therefore, it is of great significance to develop polyimide films with high thermal conductivity and high insulation. Summary of the invention

[0007] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a slurry and its preparation method and application, and a high thermal conductivity polyimide film. The present invention performs surface modification on Si4N3, blends the surface-modified Si4N3 with graphene nanosheets (GNPs), and coats the surface of the graphene nanosheets through electrostatic adsorption, and finally adds the mixed liquid to the polyamic acid solution to prepare a high thermal conductivity PI film. The method of the present invention is simple, highly operable, and provides a new option for preparing a high thermal conductivity flexible composite film.

[0008] In order to achieve the above object, the technical solution of the present invention is:

[0009] The first aspect of the present invention provides a slurry for a high thermal conductivity polyimide film, which is prepared from raw materials of the following components:

[0010] 5-25 parts of diamine monomer, 15-35 parts of dianhydride monomer, 150-250 parts of solvent, 4-10 parts of surface-modified silicon nitride, and 1-5 parts of graphene.

[0011] In some embodiments of the present invention, the diamine monomer includes one or more of m-phenylenediamine, p-phenylenediamine, m-phenylenediamine, 2,6-pyridinediamine, 2,4-pyrimidinediamine, 2,4-symmetrical triazinediamine, phenyl-symmetrical triazinediamine, o-toluenediamine, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,5-diphenyl-1,3,4-oxadiazole, 9,9-bis(4-aminophenyl)fluorene, 1,3-cyclohexanedimethylamine and 1,4-cyclohexanedimethylamine.

[0012] Preferably, the diamine monomer is one or more of m-phenylenediamine, p-phenylenediamine and 4,4'-diaminodiphenyl ether.

[0013] In some embodiments of the present invention, the dianhydride monomer includes one or more of pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, hexafluorodianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride, 3,3,4,4-diphenylsulfonetetracarboxylic anhydride, 4,4'-phenylenedioxydiphthalic anhydride, 1,2,4,5-cyclohexanetetracarboxylic anhydride and 2,3,3',4'-biphenyltetracarboxylic anhydride.

[0014] Preferably, the dianhydride monomer is one or more of pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride and hexafluorodianhydride.

[0015] In some embodiments of the present invention, the solvent is a polar solvent, including one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, tetrahydrofuran, xylene, toluene, dichloromethane and chloroform.

[0016] Preferably, the solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.

[0017] In some embodiments of the present invention, the surface-modified silicon nitride is silicon nitride modified by a silane coupling agent, and the silane coupling agent includes one or more of KH171, KH470, KH530, KH550, KH560, KH561, KH570, KH792, Z6020, Z6030, Z6040, Z6043 and Z6518.

[0018] Preferably, the silane coupling agent is one or more of KH530, KH550, KH560 and KH570.

[0019] In some embodiments of the present invention, the slurry for high thermal conductivity polyimide film is prepared from raw materials of the following components:

[0020] 10-21 parts of diamine monomer, 21-30 parts of dianhydride monomer, 180-240 parts of solvent, 4-8 parts of surface-modified silicon nitride, and 1-5 parts of graphene.

[0021] In some embodiments of the present invention, the slurry for high thermal conductivity polyimide film is prepared from raw materials of the following components:

[0022] 10-21 parts of diamine monomer, 21-30 parts of dianhydride monomer, 180-240 parts of N,N-dimethylacetamide, 4-8 parts of silicon nitride modified by silane coupling agent KH570, and 1-5 parts of graphene.

[0023] In some embodiments of the present invention, the slurry for high thermal conductivity polyimide film is prepared from raw materials of the following components:

[0024] 10-21 parts of 4,4'-diaminodiphenyl ether, 21-30 parts of pyromellitic anhydride, 180-240 parts of N,N-dimethylacetamide, 4-8 parts of silicon nitride modified by silane coupling agent KH570, and 1-5 parts of graphene.

[0025] In some embodiments of the present invention, the slurry for high thermal conductivity polyimide film is prepared from raw materials of the following components:

[0026] 10-21 parts of p-phenylenediamine, 21-30 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 180-240 parts of N,N-dimethylacetamide, 4-8 parts of silicon nitride modified by silane coupling agent KH570, and 1-5 parts of graphene.

[0027] In some embodiments of the present invention, the slurry for high thermal conductivity polyimide film is prepared from raw materials of the following components:

[0028] 10-21 parts of 4,4'-diaminodiphenyl ether, 21-30 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 180-240 parts of N,N-dimethylacetamide, 4-8 parts of silicon nitride modified by silane coupling agent KH570, and 1-5 parts of graphene.

[0029] The second aspect of the present invention provides a method for preparing the above-mentioned slurry for high thermal conductivity polyimide film, comprising the following steps:

[0030] Dispersing the diamine monomer in a solvent, adding the dianhydride monomer to carry out polymerization reaction, and obtaining a polyamic acid precursor solution;

[0031] dispersing silicon nitride in a solvent, adding a silane coupling agent, and obtaining a surface-modified silicon nitride solution;

[0032] dispersing graphene in a solvent to obtain a graphene dispersion;

[0033] The surface-modified silicon nitride solution is mixed with the graphene dispersion and then added into the polyamic acid precursor solution to obtain a slurry for a high thermal conductivity polyimide film.

[0034] In some embodiments of the present invention, the molar ratio of the diamine monomer to the dianhydride monomer is (0.1-10):1, preferably (0.8-1.2):1.

[0035] In some embodiments of the present invention, the dianhydride monomer is added in batches to prevent excessive polymerization caused by a single addition. The number of additions is 1 to 20 times, preferably 5 to 7 times.

[0036] In some embodiments of the present invention, the reaction temperature of the polymerization reaction is 0-40°C, preferably 10-20°C, the reaction time is 1-8h, preferably 4-6h, and stirring is performed during the reaction, with a stirring speed of 10-1000rpm, preferably 200-500rpm.

[0037] In some embodiments of the present invention, the solid content of the polyamic acid precursor solution is 1 to 30%, preferably 10 to 20%.

[0038] In some embodiments of the present invention, the viscosity of the polyamic acid precursor solution is 100 to 50,000 mPa·s, preferably 1,000 to 10,000 mPa·s; the molecular weight of the polyamic acid is 2,000 to 200,000, preferably 5,000 to 50,000.

[0039] In some embodiments of the present invention, the preparation method includes: ultrasonically dispersing silicon nitride and a solvent for 1 to 10 hours, preferably 2 to 4 hours, adding a silane coupling agent, and stirring in a constant temperature water bath to obtain a surface-modified silicon nitride solution.

[0040] Preferably, the mass ratio of the solvent to silicon nitride is (1-50):1, preferably (2-10):1.

[0041] Preferably, the mass ratio of the silane coupling agent to silicon nitride is 1:(1-100), preferably 1:(5-20).

[0042] Preferably, the constant temperature water bath temperature is 10-100°C, preferably 40-80°C.

[0043] Preferably, the stirring speed is 50 to 500 rpm, preferably 100 to 300 rpm.

[0044] In some embodiments of the present invention, the preparation method includes: adding graphene to a solvent and dispersing it by ultrasonic to obtain a graphene dispersion.

[0045] Preferably, in the graphene dispersion, the mass ratio between the solvent and the graphene is (1-50):1, preferably (5-10):1.

[0046] Preferably, the dispersion time of the ultrasonic dispersion is 1-60 min, preferably 10-30 min.

[0047] In some embodiments of the present invention, the surface-modified silicon nitride solution and the graphene dispersion are mixed by stirring at a speed of 100 to 1000 r / min, preferably 500 to 700 r / min.

[0048] It should be noted that the graphene is graphene nanosheets (GNPs). Graphene nanosheets and graphene are both materials composed of carbon atoms, but their structures and properties are very different. Graphene is a sp 2A new material in which hybrid connected carbon atoms are tightly adsorbed into a single-layer two-dimensional graphene-like lattice structure. Graphene nanosheets are a material formed by stacking single-layer carbon atom planar structure graphene. The present invention slowly adds the surface-modified silicon nitride solution into the graphene nanosheet dispersion and stirs at high speed to mix evenly. The surface-modified silicon nitride is coated on the surface of the graphene nanosheet by electrostatic adsorption, while improving the thermal conductivity of the polyimide film, avoiding the formation of a conductive network, and obtaining a polyimide film with both good thermal conductivity and electrical insulation properties, providing a new solution for the preparation of high thermal conductivity and electrical insulation electronic packaging materials.

[0049] In some embodiments of the present invention, after the surface-modified silicon nitride solution is mixed with the graphene dispersion, it is mixed with the polyamic acid solution at 0-40°C, preferably 20-30°C, and stirred to mix, the stirring speed is 100-500r / min, preferably 200-300r / min, and the stirring time is 2-10h, preferably 6-8h.

[0050] The third aspect of the present invention provides a use of the above-mentioned slurry for high thermal conductivity polyimide film or the slurry for high thermal conductivity polyimide film prepared by the above-mentioned preparation method in a polyimide film.

[0051] A fourth aspect of the present invention provides a high thermal conductivity polyimide film, which is obtained by scraping and drying the above-mentioned high thermal conductivity polyimide film slurry or the high thermal conductivity polyimide film slurry prepared by the above-mentioned preparation method.

[0052] It should be noted that the slurry is poured onto the surface of the substrate and evenly coated by scraping, and a high thermal conductivity polyimide film is obtained after drying. The substrate is preferably a glass plate.

[0053] In some embodiments of the present invention, the thickness of the high thermal conductivity polyimide film is 5-500 μm, preferably 10-50 μm.

[0054] In some embodiments of the present invention, the drying is carried out by heating in stages at 80°C, 120°C, 150°C, 180°C, 220°C, 260°C and 300°C, respectively, preferably at 80°C, 120°C, 180°C and 300°C; the heating time for each stage is 1-5h, preferably 1-3h for each stage.

[0055] A fifth aspect of the present invention provides an application of the above-mentioned high thermal conductivity polyimide film in electronic packaging materials and integrated electronic devices.

[0056] The beneficial effects of the present invention are:

[0057] The present invention discloses a slurry for a polyimide film with high thermal conductivity. The present invention performs surface modification on silicon nitride to improve its dispersibility in a polyimide matrix, thereby solving the problem of easy agglomeration of silicon nitride. The surface-modified silicon nitride is coated on the surface of graphene nanosheets through electrostatic adsorption, thereby improving the thermal conductivity of the polyimide film while avoiding the formation of a conductive network, thereby obtaining a polyimide film with both good thermal conductivity and electrical insulation properties, thereby providing a new solution for preparing electronic packaging materials with high thermal conductivity and electrical insulation. It has been verified that the high thermal conductivity polyimide film (thermal conductivity of 3.52W / (m·K)) prepared by the present invention can improve the thermal conductivity by more than 20 times compared with the ordinary polyimide film (thermal conductivity of 0.16W / (m·K)), which can effectively solve the problem of slow heat dissipation of the polyimide film and broaden the application range of the polyimide film.

[0058] The preparation method of the present invention is simple and has good repeatability. It avoids the loss of materials caused by the complex synthesis process and does not require expensive experimental equipment. It provides a way to efficiently and large-scale prepare high thermal conductivity polyimide films and solves the problem that the film material has poor heat dissipation, which in turn affects the overall service life of the device. It has good application scenarios in the field of high-density, high-power, and high-heat integrated electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0060] Figure 1 This is the XPS spectrum of the surface-modified silicon nitride / graphene and graphene in Example 1 of the present invention. DETAILED DESCRIPTION

[0061] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0062] Example 1

[0063] This embodiment provides a method for preparing a polyimide composite film with high thermal conductivity.

[0064] (1) Add 0.1 mol of 4,4'-diaminodiphenyl ether (20.02 g) and 167.32 g of N,N-dimethylacetamide to a flask, use a water bath to maintain the temperature at 20°C, stir at 150 r / min, stir evenly after 15 minutes, then adjust the stirring speed to 250 r / min, add 0.1 mol of pyromellitic anhydride (21.81 g), and add pyromellitic anhydride in 7 times. After each addition, wait until the reaction temperature in the flask drops to 20°C before adding the next one. After the addition is completed, continue to maintain the same temperature for 6 hours, and the polymer viscosity gradually rises to 6000 Pa.s. At this time, a polyamic acid (PAA) solution with a solid content of 20% is obtained for standby use;

[0065] (2) 5.60 g of silicon nitride and 20.90 g of N,N-dimethylacetamide were placed in a three-necked flask, 0.21 g of silane coupling agent KH570 was added, and the mixture was stirred at 200 r / min in a water bath at 80° C. for 2 h to obtain a surface-modified silicon nitride mixed solution;

[0066] (3) 2.6 g of graphene nanosheets and 9.70 g of N,N-dimethylacetamide were placed in a three-necked flask, ultrasonicated for 20 min using an ultrasonic disperser, the surface-modified silicon nitride mixed solution was added to the flask, and stirred at 300 r / min for 2 h to obtain a silicon nitride / graphene nanosheet mixed solution;

[0067] (4) Stirring the polyamic acid solution at room temperature and 300 r / min, slowly dropwise adding the silicon nitride / graphene nanosheet mixture, and continuously stirring for 6 h to obtain a uniform polyamic acid / silicon nitride / graphene solution. The solution was uniformly poured onto a glass plate, placed in an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 h, respectively, to obtain a polyimide composite film.

[0068] Example 2

[0069] This embodiment provides a method for preparing a polyimide film with high thermal conductivity.

[0070] (1) Add 0.1 mol of p-phenylenediamine (10.81 g) and 160.94 g of N,N-dimethylacetamide to a flask, use a water bath to maintain the temperature at 20°C, stir at 150 r / min, stir evenly after 15 minutes, then adjust the stirring speed to 250 r / min, add 0.1 mol of 3,3',4,4'-biphenyltetracarboxylic anhydride (29.42 g), and add biphenyltetracarboxylic anhydride in 7 times. After each addition, wait until the reaction temperature in the flask drops to 20°C before adding the next one. After the addition is completed, continue to react at the same temperature for 6 hours, and the polymer viscosity gradually rises to 4000 Pa.s. At this time, a polyamic acid (PAA) solution with a solid content of 20% is obtained for standby use;

[0071] (2) 5.60 g of silicon nitride and 20.90 g of N,N-dimethylacetamide were placed in a three-necked flask, 0.21 g of silane coupling agent KH570 was added, and the mixture was stirred at 200 r / min in a water bath at 80° C. for 2 h to obtain a surface-modified silicon nitride mixed solution;

[0072] (3) 2.6 g of graphene nanosheets and 9.70 g of N,N-dimethylacetamide were placed in a three-necked flask, ultrasonicated for 20 min using an ultrasonic disperser, the surface-modified silicon nitride mixed solution was added to the flask, and stirred at 300 r / min for 2 h to obtain a silicon nitride / graphene nanosheet mixed solution;

[0073] (4) Stirring the polyamic acid solution at room temperature and 300 r / min, slowly dropwise adding the silicon nitride / graphene nanosheet mixture, and continuously stirring for 6 h to obtain a uniform polyamic acid / silicon nitride / graphene solution. The solution was uniformly poured onto a glass plate, placed in an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 h, respectively, to obtain a polyimide composite film.

[0074] Example 3

[0075] This embodiment provides a method for preparing a polyimide film with high thermal conductivity.

[0076] (1) Add 0.1 mol of 4,4'-diaminodiphenyl ether (20.02 g) and 197.78 g of N,N-dimethylacetamide to a flask, use a water bath to maintain the temperature at 20°C, stir at 150 r / min, stir evenly after 15 minutes, then adjust the stirring speed to 250 r / min, add 0.1 mol of 3,3',4,4'-biphenyltetracarboxylic anhydride (29.42 g), and add biphenyltetracarboxylic anhydride in 7 times. After each addition, wait until the reaction temperature in the flask drops to 20°C before adding the next time. After the addition is completed, continue to maintain the same temperature for 6 hours, and the polymer viscosity gradually rises to 5000 Pa.s. At this time, a polyamic acid (PAA) solution with a solid content of 20% is obtained for standby use;

[0077] (2) 5.60 g of silicon nitride and 20.90 g of N,N-dimethylacetamide were placed in a three-necked flask, 0.21 g of silane coupling agent KH570 was added, and the mixture was stirred at 200 r / min in a water bath at 80° C. for 2 h to obtain a surface-modified silicon nitride mixed solution;

[0078] (3) 2.6 g of graphene nanosheets and 9.70 g of N,N-dimethylacetamide were placed in a three-necked flask, ultrasonicated for 20 min using an ultrasonic disperser, the surface-modified silicon nitride mixed solution was added to the flask, and stirred at 300 r / min for 2 h to obtain a silicon nitride / graphene nanosheet mixed solution;

[0079] (4) Stirring the polyamic acid solution at room temperature and 300 r / min, slowly dropwise adding the silicon nitride / graphene nanosheet mixture, and continuously stirring for 6 h to obtain a uniform polyamic acid / silicon nitride / graphene solution. The solution was uniformly poured onto a glass plate, placed in an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 h, respectively, to obtain a polyimide composite film.

[0080] Example 4

[0081] This embodiment provides a method for preparing a polyimide composite film with high thermal conductivity.

[0082] (1) Add 0.1 mol of 4,4'-diaminodiphenyl ether (20.02 g) and 167.32 g of N,N-dimethylacetamide to a flask, use a water bath to maintain the temperature at 20°C, stir at 150 r / min, stir evenly after 15 minutes, then adjust the stirring speed to 250 r / min, add 0.1 mol of pyromellitic anhydride (21.81 g), and add pyromellitic anhydride in 7 times. After each addition, wait until the reaction temperature in the flask drops to 20°C before adding the next one. After the addition is completed, continue to maintain the same temperature for 6 hours, and the polymer viscosity gradually rises to 6000 Pa.s. At this time, a polyamic acid (PAA) solution with a solid content of 20% is obtained for standby use;

[0083] (2) 4.20 g of silicon nitride and 15.68 g of N,N-dimethylacetamide were placed in a three-necked flask, 0.16 g of silane coupling agent KH570 was added, and the mixture was stirred at 200 r / min in a water bath at 80° C. for 2 h to obtain a surface-modified silicon nitride mixed solution;

[0084] (3) 4.0 g of graphene nanosheets and 14.92 g of N,N-dimethylacetamide were placed in a three-necked flask, ultrasonicated for 20 min using an ultrasonic disperser, the surface-modified silicon nitride mixed solution was added to the flask, and stirred at 300 r / min for 2 h to obtain a silicon nitride / graphene nanosheet mixed solution;

[0085] (4) Stirring the polyamic acid solution at room temperature and 300 r / min, slowly dropwise adding the silicon nitride / graphene nanosheet mixture, and continuously stirring for 6 h to obtain a uniform polyamic acid / silicon nitride / graphene solution. The solution was uniformly poured onto a glass plate, placed in an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 h, respectively, to obtain a polyimide composite film.

[0086] Example 5

[0087] This embodiment provides a method for preparing a polyimide composite film with high thermal conductivity.

[0088] (1) Add 0.1 mol of 4,4'-diaminodiphenyl ether (20.02 g) and 167.32 g of N,N-dimethylacetamide to a flask, use a water bath to maintain the temperature at 20°C, stir at 150 r / min, stir evenly after 15 minutes, then adjust the stirring speed to 250 r / min, add 0.1 mol of pyromellitic anhydride (21.81 g), and add pyromellitic anhydride in 7 times. After each addition, wait until the reaction temperature in the flask drops to 20°C before adding the next one. After the addition is completed, continue to maintain the same temperature for 6 hours, and the polymer viscosity gradually rises to 6000 Pa.s. At this time, a polyamic acid (PAA) solution with a solid content of 20% is obtained for standby use;

[0089] (2) 7.0 g of silicon nitride and 26.13 g of N,N-dimethylacetamide were placed in a three-necked flask, 0.26 g of silane coupling agent KH570 was added, and the mixture was stirred at 200 r / min in a water bath at 80° C. for 2 h to obtain a surface-modified silicon nitride mixed solution;

[0090] (3) 1.2 g of graphene nanosheets and 4.48 g of N,N-dimethylacetamide were placed in a three-necked flask, ultrasonicated for 20 min using an ultrasonic disperser, the surface-modified silicon nitride mixed solution was added to the flask, and stirred at 300 r / min for 2 h to obtain a silicon nitride / graphene nanosheet mixed solution;

[0091] (4) Stirring the polyamic acid solution at room temperature and 300 r / min, slowly dropwise adding the silicon nitride / graphene nanosheet mixture, and continuously stirring for 6 h to obtain a uniform polyamic acid / silicon nitride / graphene solution. The solution was uniformly poured onto a glass plate, placed in an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 h, respectively, to obtain a polyimide composite film.

[0092] Comparative Example 1

[0093] The polyamic acid solution of this comparative example is the same as that of Example 1.

[0094] (1) Without adding silicon nitride and graphene, the polyamic acid solution is directly and evenly poured on a glass plate, put into an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 h, respectively, to obtain a polyimide film.

[0095] Comparative Example 2

[0096] The polyamic acid solution of this comparative example is the same as that of Example 1.

[0097] (1) 5.60 g of silicon nitride and 20.90 g of N,N-dimethylacetamide were placed in a three-necked flask, 0.21 g of silane coupling agent KH570 was added, and the mixture was stirred at 200 r / min in a water bath at 80° C. for 2 h to obtain a surface-modified silicon nitride mixed solution;

[0098] (2) The polyamic acid solution was stirred at room temperature and 300 r / min, and the silicon nitride mixed solution was slowly added dropwise, and stirred continuously for 6 hours to obtain a uniform polyamic acid / silicon nitride solution. The solution was evenly poured on a glass plate, placed in an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 hour to obtain a polyimide composite film.

[0099] Comparative Example 3

[0100] The polyamic acid solution of this comparative example is the same as that of Example 1.

[0101] (1) 5.60 g of silicon nitride and 20.90 g of N,N-dimethylacetamide were placed in a three-necked flask, and stirred at 200 r / min in a water bath at 80° C. for 2 h to obtain a silicon nitride mixed solution;

[0102] (2) The polyamic acid solution was stirred at room temperature and 300 r / min, and the silicon nitride mixed solution was slowly added dropwise, and stirred continuously for 6 hours to obtain a uniform polyamic acid / silicon nitride solution. The solution was evenly poured on a glass plate, placed in an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 hour to obtain a polyimide composite film.

[0103] Comparative Example 4

[0104] The polyamic acid solution of this comparative example is the same as that of Example 1.

[0105] (1) 2.6 g of graphene nanosheets and 9.70 g of N,N-dimethylacetamide were placed in a three-necked flask and ultrasonicated for 20 min using an ultrasonic disperser to obtain a graphene mixed solution;

[0106] (2) The polyamic acid solution was stirred at room temperature and 300 r / min, and the graphene mixed solution was slowly added dropwise, and stirred continuously for 6 hours to obtain a uniform polyamic acid / graphene mixed solution. The solution was evenly poured on a glass plate, placed in an oven, and heated at 80°C, 120°C, 180°C, and 300°C for 1 hour to obtain a polyimide composite film.

[0107] Test Example 1

[0108] The polyimide composite films obtained in the above Examples 1-3, Comparative Examples 2-4 and the polyimide film obtained in Comparative Example 1 were subjected to performance tests, and the test results are shown in Table 1 below.

[0109] Table 1 Thermal conductivity test results of polyimide composite thermal conductive film and polyimide film

[0110] serial number Thermal conductivity W / (m·K) Example 1 3.52 Example 2 3.48 Example 3 3.36 Example 4 3.71 Example 5 2.38 Comparative Example 1 0.16 Comparative Example 2 1.61 Comparative Example 3 1.07 Comparative Example 4 3.16

[0111] According to the data in Table 1, it can be seen that the thermal conductivity of the pure polyimide film in Comparative Example 1 is 0.16W / (m·K), and the thermal conductivity is poor. After adding Si4N3 in Comparative Example 3, the thermal conductivity is improved to 1.07W / (m·K). In Comparative Example 2, a silane coupling agent is further added to increase the dispersibility of Si4N3 in polyimide, and the thermal conductivity of the film is further increased to 1.61W / (m·K). The reason is that the surface modification effect of the silane coupling agent enhances the interaction between silicon nitride and polyimide molecules, making Si4N3 more evenly dispersed in the system and having better thermal conductivity. In Comparative Example 4, Si4N3 is no longer added, but graphene nanosheets are added instead, and the thermal conductivity of the film is greatly increased to 3.16W / (m·K), and the thermal conductivity is significantly improved.

[0112] By comparing Examples 1-3, it can be seen that when the type and amount of thermal conductive fillers added are the same, the composite film prepared by the system of 4,4'-diaminodiphenyl ether and pyromellitic acid glycoside in Example 1 has better thermal conductivity.

[0113] By comparing Example 1 and Examples 4-5, it can be seen that, under the premise that the total mass of filler added remains unchanged, as the proportion of graphene added increases, the overall thermal conductivity of the composite material continues to increase, and in Example 4 the thermal conductivity can be increased to a maximum of 3.71 W / (m·K).

[0114] Table 2 Test results of electrical insulation properties of polyimide composite thermal conductive film and polyimide film

[0115]

[0116]

[0117] It can be seen from Table 2 that the volume resistivity of the pure polyimide film in Comparative Example 1 is 4.5*10 17 Ω·cm. After adding Si4N3 and Si4N3 modified by silane coupling agent to Comparative Example 2 and Comparative Example 3, the volume resistivity of the composite material is 4.0*10 17 Ω·cm and 3.9*10 17 Ω·cm, the resistivity decreased slightly, and the volume resistivity of the two materials was similar, proving that the modification of silane coupling agent had little effect on the overall resistivity of the material. As can be seen from Comparative Example 4, after adding graphene nanosheets instead of Si4N3, the volume resistivity of the composite material dropped significantly to 4.2*10 12 Ω·cm. The reason is that graphene has good electrical conductivity, and adding it alone as a filler will greatly reduce the electrical conductivity of the material. As can be seen from Example 1, after adding Si4N3 and graphene at the same time, the coating effect of Si4N3 hinders the graphene nanosheets from forming a conductive network in the system, so the overall resistivity of the composite material decreases less.

[0118] By comparing Examples 1-3, it can be seen that when the type and amount of thermal conductive fillers added are the same, the composite film prepared by the system of 4,4'-diaminodiphenyl ether and pyromellitic acid glycoside in Example 1 has better electrical insulation effect.

[0119] Compared with Example 1, Examples 4-5 show that when the total mass of the filler remains unchanged, the amount of graphene added is increased. Due to the small amount of silicon nitride added, it is difficult to completely cover the surface of the graphene nanosheets, resulting in a significant decrease in the volume resistivity of the composite material. For example, the volume resistivity of the material in Experimental Example 4 decreases to 6.8*10 12 Ω·cm.

[0120] According to the above experimental results, when Si4N3 modified by silane coupling agent and graphene nanosheets are added in the amount described in Experimental Example 1, the thermal conductivity of the material can be significantly improved, and silicon nitride can be completely coated on the surface of the graphene nanosheets to prevent the graphene from being exposed to form a complete conductive network and affect the electrical insulation performance of the material. Finally, the prepared composite material can have both good thermal conductivity and electrical insulation performance.

[0121] Test Example 2

[0122] XPS was used to test the graphene and the graphene / surface-modified silicon nitride material in Example 1 to analyze their surface compositions. Figure 1As can be seen from the graphene surface, there are oxygen-containing groups, so the signal peaks of C1s and O1s can be seen in the XPS spectrum. In the graphene / silicon nitride material, due to the addition of silicon nitride material, the characteristic peaks of N1s and Si2p are added to the spectrum. From the peak intensity, it can be seen that the silicon nitride content on the graphene surface is high, proving that silicon nitride can be effectively adsorbed on the graphene surface.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A slurry for a high thermal conductivity polyimide film, characterized in that: It is prepared from the following raw materials: 5-25 parts of diamine monomer, 15-35 parts of dianhydride monomer, 150-250 parts of solvent, 4-10 parts of surface-modified silicon nitride, and 1-5 parts of graphene.

2. The slurry for a high thermal conductive polyimide film according to claim 1, wherein: The diamine monomer includes one or more of m-phenylenediamine, p-phenylenediamine, m-phenylenediamine, 2,6-pyridinediamine, 2,4-pyrimidinediamine, 2,4-symmetrical triazinediamine, phenyl-symmetrical triazinediamine, o-toluenediamine, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,5-diphenyl-1,3,4-oxadiazole, 9,9-bis(4-aminophenyl)fluorene, 1,3-cyclohexanedimethylamine and 1,4-cyclohexanedimethylamine; preferably, the diamine monomer is one or more of m-phenylenediamine, p-phenylenediamine and 4,4'-diaminodiphenyl ether; Preferably, the dianhydride monomer includes one or more of pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, hexafluoro dianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride, 3,3,4,4-diphenylsulfonetetracarboxylic anhydride, 4,4'-phenylenedioxydiphthalic anhydride, 1,2,4,5-cyclohexanetetracarboxylic anhydride and 2,3,3',4'-biphenyltetracarboxylic anhydride; preferably, the dianhydride monomer is one or more of pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride and hexafluoro dianhydride; Preferably, the solvent is a polar solvent, including one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, tetrahydrofuran, xylene, toluene, dichloromethane and chloroform; preferably, the solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; Preferably, the surface-modified silicon nitride is silicon nitride modified by a silane coupling agent, and the silane coupling agent includes one or more of KH171, KH470, KH530, KH550, KH560, KH561, KH570, KH792, Z6020, Z6030, Z6040, Z6043 and Z6518; preferably, the silane coupling agent is one or more of KH530, KH550, KH560 and KH570.

3. The slurry for a high thermal conductive polyimide film according to claim 1, wherein: It is prepared from the following raw materials: 10-21 parts of diamine monomer, 21-30 parts of dianhydride monomer, 180-240 parts of solvent, 4-8 parts of surface-modified silicon nitride, 1-5 parts of graphene; Preferably, it is prepared from the following raw materials: 10-21 parts of diamine monomer, 21-30 parts of dianhydride monomer, 180-240 parts of N,N-dimethylacetamide, 4-8 parts of silicon nitride modified by silane coupling agent KH570, and 1-5 parts of graphene; Preferably, it is prepared from the following raw materials: 10-21 parts of 4,4'-diaminodiphenyl ether, 21-30 parts of pyromellitic anhydride, 180-240 parts of N,N-dimethylacetamide, 4-8 parts of silicon nitride modified by silane coupling agent KH570, and 1-5 parts of graphene; Preferably, it is prepared from the following raw materials: 10-21 parts of p-phenylenediamine, 21-30 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 180-240 parts of N,N-dimethylacetamide, 4-8 parts of silicon nitride modified by silane coupling agent KH570, and 1-5 parts of graphene; Preferably, it is prepared from the following raw materials: 10-21 parts of 4,4'-diaminodiphenyl ether, 21-30 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 180-240 parts of N,N-dimethylacetamide, 4-8 parts of silicon nitride modified by silane coupling agent KH570, and 1-5 parts of graphene.

4. A method for preparing a slurry for a high thermal conductivity polyimide film according to any one of claims 1 to 3, characterized in that: The steps include: Dispersing the diamine monomer in a solvent, adding the dianhydride monomer to carry out polymerization reaction, and obtaining a polyamic acid precursor solution; dispersing silicon nitride in a solvent, adding a silane coupling agent, and obtaining a surface-modified silicon nitride solution; dispersing graphene in a solvent to obtain a graphene dispersion; The surface-modified silicon nitride solution is mixed with the graphene dispersion and then added into the polyamic acid precursor solution to obtain a slurry for a high thermal conductivity polyimide film.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the diamine monomer to the dianhydride monomer is (0.1-10):1, preferably (0.8-1.2):1; Preferably, the dianhydride monomer is added in batches, with the number of additions being 1 to 20 times, preferably 5 to 7 times; Preferably, the reaction temperature of the polymerization reaction is 0 to 40°C, preferably 10 to 20°C, the reaction time is 1 to 8 hours, preferably 4 to 6 hours, stirring is performed during the reaction, and the stirring speed is 10 to 1000 rpm, preferably 200 to 500 rpm; Preferably, the solid content of the polyamic acid precursor solution is 1 to 30%, preferably 10 to 20%; Preferably, the viscosity of the polyamic acid precursor solution is 100 to 50,000 mPa·s, preferably 1,000 to 10,000 mPa·s; the molecular weight of the polyamic acid is 2,000 to 200,000, preferably 5,000 to 50,000.

6. The preparation method according to claim 4, characterized in that: The preparation method comprises: ultrasonically dispersing silicon nitride and a solvent for 1 to 10 hours, preferably 2 to 4 hours, then adding a silane coupling agent, stirring in a constant temperature water bath, and obtaining a surface-modified silicon nitride solution; preferably, the mass ratio of the solvent to silicon nitride is (1 to 50):1, preferably (2 to 10):1; preferably, the mass ratio of the silane coupling agent to silicon nitride is 1:(1 to 100), preferably 1:(5 to 20); preferably, the temperature of the constant temperature water bath is 10 to 100° C., preferably 40 to 80° C.; preferably, the stirring speed is 50 to 500 rpm, preferably 100 to 300 rpm; Preferably, the preparation method comprises: adding graphene to a solvent and ultrasonically dispersing to obtain a graphene dispersion; preferably, in the graphene dispersion, the mass ratio between the solvent and the graphene is (1-50):1, preferably (5-10):1; preferably, the dispersion time of the ultrasonic dispersion is 1-60 min, preferably 10-30 min.

7. The preparation method according to claim 4, characterized in that: The surface-modified silicon nitride solution and the graphene dispersion are mixed by stirring at a speed of 100 to 1000 r / min, preferably 500 to 700 r / min; Preferably, after the surface-modified silicon nitride solution is mixed with the graphene dispersion, it is mixed with the polyamic acid solution at 0 to 40° C., preferably 20 to 30° C., and mixed by stirring. The stirring speed is 100 to 500 r / min, preferably 200 to 300 r / min, and the stirring time is 2 to 10 h, preferably 6 to 8 h.

8. Use of the slurry for high thermal conductivity polyimide film according to any one of claims 1 to 3 or the slurry for high thermal conductivity polyimide film prepared by the preparation method according to any one of claims 4 to 7 in polyimide film.

9. A high thermal conductivity polyimide film, characterized in that: The high thermal conductivity polyimide film slurry is obtained by flattening and drying the high thermal conductivity polyimide film slurry described in any one of claims 1 to 3 or the high thermal conductivity polyimide film slurry prepared by the preparation method described in any one of claims 4 to 6. Preferably, the thickness of the high thermal conductivity polyimide film is 5-500 μm, preferably 10-50 μm; Preferably, the drying is carried out by heating in stages, heating at 80°C, 120°C, 150°C, 180°C, 220°C, 260°C and 300°C respectively, preferably heating at 80°C, 120°C, 180°C and 300°C; the heating time for each stage is 1-5h, preferably 1-3h for each stage.

10. Use of the high thermal conductivity polyimide film according to claim 9 in electronic packaging materials and integrated electronic devices.